Green Logistics: A System of Methods and Instruments - Part 2 - Aleksandr Rakhmangulov; Aleksander Sladkowski; Nikita Osintsev; Dmitri Muravev (Naše More (Dubrovnik), 2018)
The first part of this paper presents the review on most authoritative studies in the field of sustainable development and green logistics, as well as a new approach to achieve the goals of sustainable development in the operation of logistics and transport systems. The second part reflects the results of systematisation of methods and instruments of green logistics, used to achieve the goals of sustainable development. The application of the presented approach to achieving the goals of sustainable development could form the balanced programs to raise environmental performance and effectiveness of supply chains’ operation, and systemic implementation of methods and instruments of green logistics will provide achieving the goals of sustainable development.